PENGARUH KAPSUL IKAN GABUS TERHADAP PENYEMBUHAN LUKA PERINIUM PADA IBU NIFAS - Dina Syafputri; Risqi Utami (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2026)
Perineal wounds are one of the health problems that often occur in postpartum mothers and can cause pain, activity limitations, and slow recovery. The wound healing process is influenced by nutritional status, especially protein and albumin. Snakehead fish (Channa striata) is known to have high albumin and protein content which plays an important role in tissue regeneration so it has the potential to accelerate wound healing. This study aims to determine the effect of administering snakehead fish capsules on the duration of perineal wound healing in postpartum mothers. The study used a quasi-experimental design with a post-test only control group design approach. At the Baloi Permai Community Health Center from February to August 2025. The population in this study were postpartum mothers, a sample of 32 respondents consisting of an intervention group given snakehead fish capsules and a control group. Data analysis using SPSS Data on the duration of perineal wound healing were analyzed using an independent t-test with a significance level of 0.05. The average duration of perineal wound healing in the control group was 7.31 days, while in the intervention group it was 4.88 days. The mean difference of 2.42 days was statistically significant with a p-value of 0.000 (α < 0.05). This indicates that snakehead fish capsules significantly accelerated perineal wound healing in postpartum women. This study recommends the use of snakehead fish capsules as a non-invasive, locally sourced complementary therapy to support postpartum recovery. Keywords: Snakehead Fish Capsules, Perineal Wounds, Postpartum